Acute Otitis Media: Diagnostic and therapeutic advances and perspectives in the contemporary era (Research, Society and Development, 2024)
Introduction: Acute otitis media is a common condition, especially in children, and one of the main causes of pediatric consultations. Objectives: This study aims to review contemporary and multidisciplinary approaches to the diagnosis and treatment of acute otitis media, highlighting recent advances and scientific gaps. Materials and Methods: This is an integrative literature review on the general clinical characteristics of acute otitis media. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Acute Otitis Media”; “Propaedeutics”; “Treatment” was cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: an analysis of recent publications reveals that, pathophysiologically, the disease is related to alterations in the auditory tube and upper respiratory tract infections. Clinically, it manifests with intense pain in the ear, fever and, in more severe cases, tympanic perforation. Diagnosis is based on a combination of clinical findings and otoscopy, while treatment involves the judicious use of antibiotics and surgical intervention in recurrent cases. The results indicate the need for prospective studies that address the effectiveness of current treatments and epidemiological investigations that allow for a broader understanding of the disease. Conclusion: We conclude that acute otitis media should be treated comprehensively, taking into account anatomical, pathophysiological and clinical aspects, with the aim of providing resolutive and humanized care.